Penilaian kesesuaian kaedah fotogrametri digital jarak dekat untuk pengukuran objek tiga dimensi - Hashim, Khairil Afendy (2009)
This study concentrates on the use of digital close range photogrammetric method. This method can be used in various field such as industrial, engineering, medical, archaeology and architecture. The aim of this study is to investigate the use of digital photogrammetric method for measurement of 3D object and generating 3D model. In this study, four different test objects were used which comprised of the replica of bottle, cylinder pipe, Multi Mission Vessel (MMV) hull model and four wheel drive vehicle. For each test object, retro-reflective targets are sticked to it. Then, digital images surrounding the test object were acquired using digital camera and convergent configuration. After the imaging process, these images were processed using two digital close range photogrammetric softwares known as Australis and PhotoModeler. The output from the two softwares is 3D coordinates. Next the 3D coordinates were input into modeling software to generate 3D model of the test object. For accuracy assessment of measurement, geodetic method and VSTARS system are used. Results of the study showed that the mean accuracy for Australis is between ±0.023 mm to ±0.499, while the mean accuracy for PhotoModeler is between ±0.106 mm to ±1.361 mm. In conclusion, this study shows that digital close range photogrammetric method can be used for measurement of 3D object and generating 3D model.